Reading sideways : the queer politics of art in modern American fiction - Seitler, Dana (Fordham University Press, 2019)
Reading Sideways explores the role various art forms played in American literary fiction in direct relation to the politics of gender and sexuality at the turn of the century. Each chapter takes a different art form as its object: sculpture, portraiture, homecraft, and opera, which appear in the major works of the period central to questions of gender, race, and sexuality, including those by Henry James, Davis, Willa Cather, Du Bois, Sarah Orne Jewett, and Mary Wilkins Freeman.